Le Corbusier: urban visions through thresholds - Fontana, Maria Pia; Mayorga, Miguel; Roa, Margarita (Journal of Architecture and Urbanism, 2016)
In Le Corbusier’s work the threshold is represented like a revealing and enigmatic space that define the relations of the limit or boundary, the separation and the union between the buildings and the urban spaces, and the space that defines, qualifies and characterises the minimum condition of urbanity of any work of architecture, irrespective of its use or scale. Through an analysis of the draws based on the study of the six notebooks of The Voyage d’Orient (1911), and of the study of the urban settings visited, we verified that the threshold is, for Le Corbusier, a space or sequence of spaces organised under the idea of “plan” of variable thickness or extension, that includes both criteria and guidelines of order as well as solutions for managing the limits or boundaries in architecture, as well as its relation with space and the involvement with its surroundings, that is to say, we have also focused on highlighting how the architecture in itself, attends to an order that as well as being articulated and unitary, is extended by means of doors, frames, courtyards, terraces, sheds and exterior spaces, that incorporate both the nearby urban landscape as well as the distant cityscape.